THE EFFORTS TO IMPROVE THE QUALITY OF EDUCATORS IN NAVAL TECHNOLOGY COLLEGE (STTAL) ENVIRONMENT TO EARN EXCELLENT SOLDIER TECHNOCRATS - Edy Widodo; Okol Sri Suharyo; Anton Nugroho (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
Naval Technology College (STTAL) is an element of implementing and fostering a central implementing agency which is located directly under the STTAL Commander. STTAL has the main task of assisting Chief of Naval Staff in carrying out the required education for marine science and technology high schools and fostering all levels of its strength including its organic supporting facilities and infrastructure to support the main tasks of the Navy. For improving STTAL's world-class reputation, a development concept is needed. The development concept includes education, research, community service, human resources, infrastructure and facilities as well as institutional capacity. However, Human Resources (HR) plays a key role in a university, namely lecturers or educators and students. Lecturers or educators play a role in human resource development. Several efforts can be made to improve human resources, namely by increasing the qualifications of lecturers and improving the academic or research abilities of lecturers with the concept of training or mentoring, including incentives or grants. Efforts to improve the quality of educators and education personnel cannot be separated from the following important aspects, namely salaries and welfare standards that are adequate for their lives, qualification standards, Keywords: Human Resource, Naval Education, and Naval Technology College (STTAL).